English major community college presidents: a narrative inquiry - Frankland, Tammy, author; Carlson, Laurie A., advisor (Colorado State University. Libraries, 2009)
The purpose of this narrative inquiry was to discover how community college presidents who were undergraduate English majors (English major presidents) construct the stories of their academic and professional journeys. Six presidents shared their stories in private, audio-taped interviews. Narrative inquiry was employed as a qualitative method for analysis and interpretation of data, and themes were drawn from each president's story and then all presidents' stories were compared. For the findings, I used literary pseudonyms to invoke parallels to the presidents' lives, and I first presented the presidents' stories individually to capture their voices and highlight differences in their experiences. Then I synthesized my findings using three themes-boundaries, connections, and transformations-as an interpretative framework. The selected presidents crossed boundaries, made connections to ideas and people, and transformed their thoughts and actions as found in the descriptions of their academic and professional experiences. Data analyses determined that the content and context of English major presidents' stories uncovered relationships among their experiences, their beliefs, about higher education's purpose, and their understanding of the community college mission. The meaning and significance of English major presidents' experiences have implications for community college leaders, community college constituents, other researchers, and the broader academic community. The findings provide access to English major presidents' self-understanding about how their academic experiences affect their perception and description of community colleges and their leadership practices. The selected presidents illuminated their relationships to higher education and narrated how their educational endeavors have influenced their personal and professional lives. In particular, they believe their past study of literature helps them understand people and informs their present leadership practices. Their self-reflective explorations provide an additional lens to view the purposes of higher education, the comprehensive community college mission, and community college leadership.
Keywords: community college leadership; community college mission; community college presidents; English major; narrative inquiry; undergraduate; community college education; school administration; higher education; college presidents; inquiry method; educational administration